Hydrogen and methane breath test results are negatively associated with IBS and may reflect transit time in post‐surgical patients. Issue 6 (12th November 2020) - Essa, Hani; Hamdy, Shaheen; Green, Darren; Lal, Simon; McLaughlin, John; Hoffmann, Sandra; Leitao, Eugena; Paine, Peter
Abstract: Background: Contention surrounds hydrogen and methane breath tests as putative measures of small intestinal bacterial overgrowth. We aimed to explore the clinical characteristics associated with positive and negative results to help clarify their role. Methods: 525 glucose hydrogen/methane breath tests completed over 3 years were analyzed to look for positively and negatively associated predictive factors. Characteristics such as height and weight and underlying medical conditions, medications, and surgical history were collated. Key results: There were 85 and 42 positive hydrogen and methane tests, respectively. Patients with irritable bowel syndrome (IBS) (HR = 0.17, p  = 0.004) and those with a higher body mass index (HR = 0.93, p  = 0.004) were significantly less likely to have a positive test. Patients who underwent the test post‐surgically were significantly more likely to have a positive test (HR = 2.76, p  = 0.001). A sub‐analysis of post‐surgical patients by type and region of surgical resection demonstrated that none were statistically more likely than the next to have a positive test. However, for the surgical group as a whole the number of motility‐depressing drugs taken (such as opioids) was associated with a significantly decreased likelihood of a positive test (HR = 0.752, p  = 0.045). Conclusion: Our data suggest that patients with a diagnosis of IBS are statistically less likely to have a positive test and it is of limited utility in this group. Post‐surgical patients are more likely to have a positive test, possibly secondary to fast transit rather than bacterial overgrowth, as suggested by a significantly negative association with motility‐suppressing drugs in this sub‐group. Abstract : Hydrogen and methane breath test results are negatively associated with IBS and may reflect transit time in post‐surgical patients. SIBO, Small intestinal bacterial overgrowth; IBS, Irritable bowel syndrome; HR, Hazard ratio.